Building Scalable Business Models - Nielsen, Christian; Lund, Morten; Zott, Christoph; Huy, Quy; Oyon, Daniel; Sinfield, Joseph; Volberda, Henk; Bingham, Christopher; Oshri, Ilan; Spieth, Patrick; Gassmann, Oliver; Frankenberger, Karolin; et al. (MIT Sloan Management Review, 2018)
Business model innovation has become a hot topic in management circles, and understandably so. No management activity is more important than having clarity about how the organization creates, delivers, and captures value. It requires, among other things, knowing what customers want, how value can be best delivered, and how to enlist strategic partners to achieve maximum benefit. Although the ability to develop strong value propositions can enable companies to "get by, " the authors argue that many of today's most successful businesses are those that can place themselves in the "sweet spot" of business model scalability. If managers are incapable of factoring scalability attributes into their business model design, they risk being left behind, much the way bookstores owned by Borders Group Inc. were eclipsed by Amazon.com Inc. In the course of their research, the authors identified five patterns by which companies can achieve scalability. The first pattern involves adding new distribution channels. The second entails freeing the business from traditional capacity constraints. The third involves outsourcing capital investments to partners that, in effect, became participants in the business model. The fourth is having customers and other partners assume multiple roles in the business model. And the fifth pattern is to establish platform models in which even competitors may become customers. Based on these patterns, the authors developed a framework for identifying potential levers for business model scalability along with a road map that managers can use to improve their business models. Over and above the need to create value propositions that are difficult for competitors to replicate, managers need to develop business models that are capable of achieving positive returns and accelerating returns on the investments made. Merely identifying synergies, the authors note, doesn't necessarily lead to improvements in business model scalability. They write: "To achieve scalability, managers and entrepreneurs need to remove capacity constraints. They have opportunities to do this in a variety of ways: by collaborating with partners; by encouraging partners to play multiple roles in the business model; by creating platforms to attract new partners; or even by working with current competitors."